The Effect of Health Education on The Behavior of Early Handling of Injuries With The Rice Method In Futsal Players - Purwacaraka, Manggar; Islamy, Aesthetica; Farida, Farida; Anggraini, Ria; Lasman, Lasman (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Futsal game is one type of sport with physical activityand high risk of injury. Accuracy in providing first aid is influenced by the helper’s behavior. Help Â optimal and appropriate can reduce the worsening of the injured area. The purpose of the research Â This objective is to determine the effect of health education on early injury management behavior using the RICE method for futsal players. The research design used was the Pre Experiment with the One-Group Pre-post Test Design approach. The population of this study is all futsal players in Selorejo Village, Ngunut District, Tulungagung Regency, totaling 33 people. The research sample was all futsal players in Selorejo Village, Ngunut District, Tulungagung Regency, totaling 33 respondents. Research instrument form questionnaire sheet. Data processing in the form of editing, coding, scoring, tabulating, and data analysis using the Wilcoxon non-parametric testtest with the SPSS program. The results of this study indicate that the behavior of handling injuries before being given health education who have good behavior amounted to 7 respondents (21%). While the behavior of handling injuries after being given health education, most of them had good behavior with a total of 16 respondents (49%). Statistical test results obtainedÏ value 0.003 with Î± 0.05. This study proves that there is an effect of health education on early injury handling behavior with the RICE method for futsal players in Selorejo Village, Ngunut District, Tulungagung Regency. Therefore, providing health education for early treatment of injuries using the RICE method is an alternative solution that can be applied in providing health education to futsal players because it is proven to be able to improve the behavior of futsal players in treating early injuries.